Incremental Value of Cocktail 18F-FDG and 18F-NaF PET/CT Over 18F-FDG PET/CT Alone for Characterization of Skeletal Metastases in Breast Cancer. (May 2017) - Roop, Mohan J.; Singh, Baljinder; Singh, Harmandeep; Watts, Ankit; Kohli, Pavneet S.; Mittal, Bhagwant R.; Singh, Gurpreet
Abstract : Purpose: The aim of this study was to evaluate the incremental value of cocktail 18 F-FDG/ 18 F-NaF PET/CT over 18 F-FDG PET/CT alone for detection of skeletal metastases in breast cancer patients. Methods: Seventy patients with locally advanced/recurrent breast cancer were prospectively included. All patients underwent whole-body 18 F-FDG PET/CT and cocktail 18 F-FDG/ 18 F-NaF PET/CT within a span of 1 week. Both studies were evaluated to detect presence of skeletal/marrow metastases on PET/CT images by 2 nuclear medicine physicians. Clinical and radiological correlation/follow-up was used as criterion standard. Results: Of 70 patients, 50 (71.0%) had locally advanced breast cancer, and 20 had recurrent breast cancer. On patient-wise analysis, both cocktail PET/CT and 18 F-FDG PET/CT identified skeletal/marrow lesions in 23 (32.8%) of 70 patients. In 8 patients (11.4%), only cocktail PET/CT identified skeletal/marrow lesions, whereas 18 F-FDG PET/CT was negative. In the rest of the 39 patients (55.8%), no skeletal/marrow lesion was identified on both scans. Good correlation was noted between cocktail PET/CT and 18 F-FDG PET/CT results ( r = 0.785, P < 0.0001). Cocktail PET/CT detected lesions in significantly more number of patients than 18 F-FDG PET/CT alone ( P = 0.007). On lesion-wise analysis, cocktail PET/CT detected more number of lesions in 20 patients as compared with 18 F-FDG-PET/CT alone. Both scans detected same number of lesions in the rest of 11 patients with positive findings. A total of 32 additional lesions were identified on cocktail PET/CT imaging as compared with 18 F PET/CT alone ( P < 0.0001). Conclusions: Cocktail 18 F-FDG and 18 F-NaF PET/CT is superior to 18 F-FDG PET/CT alone for the detection of skeletal/marrow metastases in breast cancer. It can be a better alternative to 18 F-FDG PET/CT alone in facilities where both tracers are available.